Coastal tourism, environment, and sustainable development - a road map - Noronha, Ligia (2012)
The question of sustainability is particularly appropriate in the context of coastal tourism, which is an activity at the interface of humans, land, and water. In this book, we are not directly engaging in the debate on sustainability. While we have the broader concerns of sustainability in mind, our focus here is on environmental sustainability, by which we mean a path of tourism development that lasts, in that it does not stress the health of the coastal ecosystems of interest, in terms of their ability to provide humans with the goods and services that are required for their continued well-being over time.